Anti-fatigue special carbon-based foam material, preparation method thereof and application of anti-fatigue special carbon-based foam material in battery

By using a combination of three-dimensional foam carbon carrier and functional metal particles in zinc ion batteries, the problem of zinc dendrites and battery failure in extreme environments is solved, and high cycle life and electrochemical performance is improved. A feasible solution for deep-sea energy storage applications.

CN119208613APending Publication Date: 2024-12-27BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410727460.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During repeated charging and discharging of zinc ion batteries, uncontrollable reactions to zinc dendrites and hydrogen evolution are easily formed, affecting their long cycle and safety performance, and it is difficult to withstand changing pressure in extreme environments, resulting in battery failure.

Method used

Using a combination of three-dimensional foam carbon carrier and functional metal particles, the fatigue-resistant special carbon-based foam materials are prepared through hydrothermal assembly and ice crystal stencil extrusion technology, providing high elasticity and mechanical strength, and induced zinc deposition through functional particles to reduce the content of Nuclear overpotential promotes uniform deposition of metal zinc.

Benefits of technology

It achieves high cycle life and electrochemical performance in extreme environments, effectively improving the battery failure problem caused by load-holding fatigue in traditional electrode materials. Zinc ion batteries show a long cycle life of more than 2,500 times at high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208613A_ABST
    Figure CN119208613A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-fatigue special carbon-based foam material, a preparation method thereof and an application of the anti-fatigue special carbon-based foam material in a battery. The anti-fatigue special carbon-based foam material comprises a three-dimensional foamy carbon carrier and optional functional particles loaded on the three-dimensional carbon carrier, the functional particles are metal nanoparticles that can provide additional zinc-philic sites, thereby inducing zinc deposition. The anti-fatigue special carbon-based foam material has good electrochemical performance and mechanical performance at the same time, energy storage application in an extreme environment is achieved, and the problem that a battery fails due to the fact that a traditional electrode material cannot bear load holding fatigue is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy and nano material preparation, and further to an anti-fatigue special carbon-based foam material and a preparation method thereof and application in batteries. Background Art

[0002] Energy storage technology is one of the key technologies to promote the clean and efficient use of energy in the world. Especially under extreme conditions, the development of energy storage devices is full of opportunities and challenges. For example, in the field of deep-sea exploration, energy storage equipment must not only provide sufficient energy supply, but also fight fatigue and avoid battery failure in the face of ever-changing pressure.

[0003] Zinc-ion batteries have attracted widespread attention due to their environmentally friendly characteristics of using aqueous solutions as electrolytes, especially in deep-sea energy storage and extreme environmental conditions. However, during repeated charging and discharging, the zinc metal negative electrode is prone to form uncontrollable zinc dendrites and side reactions such as hydrogen evolution, which seriously affect the long cycle and safety performance of the battery. In addition, zinc-ion batteries need to be able to work normally under changing pressure conditions to meet the requirements of deep-sea equipment energy storage. Therefore, special designs are required to achieve dendrite-free zinc deposition and improve the ability to withstand load-holding fatigue under extreme conditions.

[0004] In recent years, the research and development of nanoscale carbon materials in energy storage and conversion devices has made phased progress. Among them, two-dimensional graphene materials have both high mechanical properties and excellent conductivity, and are expected to meet the requirements for zinc metal negative electrode carriers for extreme environment energy storage devices; but two-dimensional graphene materials are planar structures and cannot provide sufficient space for zinc deposition, cannot reduce current density, and easily lead to zinc dendrites.

[0005] Therefore, it is necessary to develop electrode materials with better performance. Summary of the invention

[0006] In order to solve the problems arising in the prior art, the present invention proposes a fatigue-resistant special carbon-based foam material, a preparation method thereof, and an application in a battery. The three-dimensional foam carbon carrier provided by the present invention has high elastic mechanical properties and can withstand load-holding fatigue; in particular, the three-dimensional foam carbon carrier and the functional metal particles loaded thereon have a synergistic effect, which can further improve the mechanical properties of the three-dimensional foam carbon carrier and meet the strength requirements of the battery carrier material in extreme environments. In addition, in addition to being able to improve the mechanical properties of the three-dimensional foam carbon carrier, the functional particles loaded by the three-dimensional foam carbon carrier can also induce zinc deposition, reduce nucleation overpotential, and promote uniform deposition of metallic zinc, thereby effectively improving the electrochemical properties of the electrode material. Therefore, the fatigue-resistant special carbon-based foam material of the present invention has both good electrochemical and mechanical properties, realizes energy storage applications in extreme environments, and effectively improves the problem that traditional electrode materials cannot withstand load-holding fatigue, resulting in battery failure.

[0007] One of the purposes of the present invention is to provide a fatigue-resistant special carbon-based foam material, which comprises a three-dimensional foam carbon carrier and optionally functional particles loaded on the three-dimensional carbon carrier; the functional particles are metal nanoparticles that can provide additional zinc-philic sites to induce zinc deposition.

[0008] In the anti-fatigue special carbon-based foam material described in the present invention, preferably,

[0009] The functional particles are selected from at least one of tin, copper or silver nanoparticles; and / or,

[0010] The loading amount of the functional particles on the three-dimensional foam carbon carrier is 2wt% to 20wt%; for example, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20wt%; and / or,

[0011] The pore size of the three-dimensional foam carbon carrier ranges from 20 μm to 300 μm.

[0012] The second object of the present invention is to provide a method for preparing an anti-fatigue special carbon-based foam material, comprising the following steps:

[0013] After introducing a bubble template into an optional solution containing a functional particle precursor and a carbon material aqueous solution, hydrothermal assembly is performed; freezing the hydrothermally assembled material and introducing it into an ice crystal template and extruding it to obtain a three-dimensional foam carbon carrier or the anti-fatigue special carbon-based foam material; optionally loading functional particles onto the three-dimensional foam carbon carrier; obtaining the anti-fatigue special carbon-based foam material;

[0014] The anti-fatigue special carbon-based foam material described in one of the objectives of the present invention is preferably prepared by the method described in the second objective of the present invention.

[0015] In the method for preparing the anti-fatigue special carbon-based foam material of the present invention, preferably, the following steps are included:

[0016] Step (1): mixing an optional solution containing a functional particle precursor with an aqueous solution of a carbon material; and then uniformly mixing with a reducing agent and a surfactant to prepare a foamed carbon material solution having abundant air microbubbles;

[0017] Step (2): hydrothermally assembling the foam carbon material solution to obtain a three-dimensional foam carbon hydrogel;

[0018] Step (3): freezing, extruding, thawing, and drying the three-dimensional carbon foam hydrogel to obtain a three-dimensional carbon foam carrier or the anti-fatigue special carbon-based foam material;

[0019] Optional step (4): after mixing the reducing agent and the solution containing the functional particle precursor evenly, add an optional hydrothermal solvent and mix evenly; then add the slices of the three-dimensional foam carbon carrier to react, wash, dry, and optionally calcine in a reducing atmosphere; to obtain the anti-fatigue special carbon-based foam material.

[0020] In the preparation method provided by the present invention, an improved sol-gel method is used, bubbles and ice crystals are used as double templates, and a compression process is coordinated to obtain a carbon-based foam material with ultra-high compressive strength.

[0021] In the method for preparing the anti-fatigue special carbon-based foam material of the present invention, preferably,

[0022] In step (1),

[0023] The carbon material used is a carbon material having self-assembly and / or gelation capabilities; preferably, the carbon material is selected from at least one of graphene oxide (GO), carbon nanotubes (CNT) or transition metal carbides (MXene); and / or,

[0024] The solution containing the functional particle precursor in step (1) is a solution containing at least one of silver, copper and tin metal ions, preferably at least one of a silver ammonia solution, a copper ammonia solution or a potassium stannate solution; and / or,

[0025] The surfactant is selected from at least one of sodium dodecyl sulfate (SDS), polyvinyl pyrrolidone, alkyl glycoside, polyethylene glycol ether or lauryl alcohol chloride; and / or,

[0026] The reducing agent is selected from at least one of ascorbic acid (AA), hydrazine hydrate or urea; and / or,

[0027] In step (1), the solution containing the reducing agent is first injected and mixed evenly, and then the solution containing the surfactant is added and mixed evenly; preferably, the injection rate is 0.02-0.15 mL min -1 , more preferably 0.03 to 0.1 mL min -1 and / or,

[0028] In step (1), the mixing is carried out by vigorous stirring; preferably, the stirring speed is 500-3000 rpm, more preferably 1600-2400 rpm; for example, 500, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000, 2200, 2400, 2600, 2800, 3000 rpm; and / or, the stirring time is 2-30 min, preferably 2-15 min; for example, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30 min; and / or,

[0029] The ratio of the carbon material to the surfactant is (30-120) mg: (0.5-5) mg; preferably (50-80) mg: (1.5-3) mg; for example, (30, 40, 50, 60, 70, 80, 90, 100, 110, 120) mg: (0.5, 1, 2, 3, 4, 5) mg; and / or,

[0030] The ratio of the carbon material to the functional particle precursor is (30-120) mg: (10-140) mg; preferably (50-80) mg: (10-30) mg; for example, (30, 40, 50, 60, 70, 80, 90, 100, 110, 120) mg: (10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140) mg; and / or,

[0031] The amount ratio of the carbon material to the reducing agent is (30-120) mg: (40-180) mg; preferably (50-80) mg: (60-130) mg; for example, (30, 40, 50, 60, 70, 80, 90, 100, 110, 120) mg: (40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180) mg; and / or,

[0032] The mass volume ratio of the carbon material to the total volume of the solvent used in the system of step (1) is (30-120) mg: (5-15 mL).

[0033] In the method for preparing the anti-fatigue special carbon-based foam material of the present invention, preferably,

[0034] In step (2),

[0035] The hydrothermal assembly temperature is 50-120°C, preferably 60-100°C; for example, 50, 60, 70, 80, 90, 100, 110, 120°C; and / or,

[0036] The hydrothermal assembly time is 2 to 24 hours, preferably 5 to 15 hours; for example, 2, 4, 5, 8, 10, 12, 15, 18, 20, 22, 24 hours; and / or,

[0037] In step (3),

[0038] The freezing temperature is -50 to 15°C, preferably -30 to 15°C; for example, -50, -40, -30, -20, -10, 0, 5, 10, 15°C; and / or,

[0039] The freezing time is 2 to 20 hours, preferably 4 to 15 hours; for example, 2, 4, 5, 8, 10, 12, 15, 18, 20 hours; and / or,

[0040] The extrusion refers to extrusion to 10% to 50% of the original height; for example, 10%, 20%, 30%, 40%, 50%, and / or

[0041] The thawing temperature is room temperature; and / or,

[0042] The drying is air drying at room temperature.

[0043] In the method for preparing the anti-fatigue special carbon-based foam material of the present invention, preferably,

[0044] In step (4),

[0045] The hydrothermal solvent is selected from at least one of ethanol and water; and / or,

[0046] The reducing agent is selected from at least one of ascorbic acid (AA), hydrazine hydrate or urea; and / or,

[0047] The solution containing the functional particle precursor in step (4) is a solution containing at least one of silver, copper, and tin metal ions, preferably at least one of a silver ammonia solution, a copper ammonia solution, or a potassium stannate solution; and / or,

[0048] In step (4), the mass ratio of the functional particle precursor to the reducing agent is (1-200) mg: (40-180) mg; preferably (5-150) mg: (60-130) mg; for example, (1, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200) mg: (40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180) mg and / or,

[0049] The mass ratio of the functional particle precursor to the hydrothermal solvent is (1-200) mg: (10-80) g; preferably (5-150) mg: (20-40) g; for example, (1, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200) mg: (10, 20, 30, 40, 50, 60, 70, 80) mg; and / or,

[0050] The mass ratio of the functional particle precursor to the three-dimensional foam carbon carrier is (1-200) mg: (3-130) mg; preferably (5-150) mg: (3-100) mg; for example, (1, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200) mg: (3, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130) mg; and / or,

[0051] In step (4), the reaction is a hydrothermal reaction or a reaction at room temperature. Preferably, the temperature of the hydrothermal reaction is 80 to 200° C.; preferably 80 to 170° C.; and / or, the time of the hydrothermal reaction is 1 to 24 hours; preferably 1 to 12 hours; and / or,

[0052] The reducing atmosphere at least includes hydrogen; the calcination temperature is 500 to 800° C., preferably 600 to 700° C.; and / or,

[0053] The calcination time is 1 to 6 hours, preferably 1 to 4 hours.

[0054] According to an embodiment of the present invention, the area of ​​the slice of the three-dimensional foam carbon support is 0.7-2 cm 2 ;Thickness is 100-1000um.

[0055] According to an embodiment of the present invention, the fatigue-resistant special carbon-based foam material can resist volume deformation caused by a rapid high-load impact process and maintain structural stability. Exemplarily, the special carbon-based foam material can recover to its original state after a certain impact.

[0056] The third object of the present invention is to provide an anti-fatigue special carbon-based foam material as described in one of the objects of the present invention or an anti-fatigue special carbon-based foam material prepared by the method described in the second object of the present invention, and its application in a battery, preferably in a zinc ion battery, and more preferably as a zinc metal negative electrode carrier.

[0057] The fourth object of the present invention is to provide a zinc metal negative electrode carrier, the material of the zinc metal negative electrode carrier includes the anti-fatigue special carbon-based foam material described in one of the objects of the present invention or the anti-fatigue special carbon-based foam material prepared by the method described in the second object of the present invention.

[0058] The fifth object of the present invention is to provide a zinc ion battery, wherein the material of the zinc metal negative electrode of the zinc ion battery includes the anti-fatigue special carbon-based foam material described in one of the objects of the present invention or the anti-fatigue special carbon-based foam material prepared by the method described in the second object of the present invention.

[0059] According to an embodiment of the present invention, the zinc ion battery is -1 It shows a long cycle life of more than 2500 times under high current density conditions.

[0060] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0061] Beneficial effects of the present invention

[0062] 1. The present invention provides a method for preparing a high-strength and fatigue-resistant special carbon-based foam material, which adopts a dual-template method, controls the size of two templates, namely, bubbles and ice crystals, by controlling the stirring rate and time, forms a hydrogel by hydrothermal reduction, introduces an ice crystal template by freezing, and cooperates with extrusion processing to form a high-strength and fatigue-resistant special carbon-based foam material.

[0063] 2. The special carbon-based foam material prepared by the present invention can be used as a zinc metal negative electrode carrier to achieve uniform and controllable zinc nucleation and growth, and effectively inhibit the uncontrollable zinc deposition / stripping behavior during the cycle. The full battery assembled using the present invention as a zinc metal negative electrode carrier has a high conductivity at 10A g -1 It still shows a long cycle life of more than 2500 times at a high current density, providing a feasible idea for the design of zinc metal anode carriers in extreme environments.

[0064] 3. In the special carbon-based foam material prepared by the present invention, the functional particles can not only improve the electrochemical properties of the electrode material, but also improve the mechanical properties of the three-dimensional foam carbon carrier (the functional particles and the three-dimensional foam carbon carrier (such as GO) have a synergistic effect, which can further improve the mechanical properties of the three-dimensional foam carbon carrier), thereby realizing energy storage applications in extreme environments and effectively improving the problem that traditional electrode materials cannot withstand load-bearing fatigue, leading to battery failure. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 It is a field emission scanning electron microscope (FESEM) cross-sectional view (left) and a transmission electron microscope (TEM) (right) of the reduced graphene oxide foam (GF) precursor prepared in Example 1 of the present invention;

[0066] Figure 2 is a plan view of the FESEM of the tin-supported reduced GO foam (SGF) prepared in Example 2 of the present invention (right);

[0067] Figure 3 is the X-ray diffraction pattern (XRD) of SGF prepared in Example 2 of the present invention;

[0068] Figure 4 The FESEM cross-sectional view before compression (left) and after compression (middle) of the silver-loaded reduced GO foam (AGF) prepared in Example 3 of the present invention, as well as the morphology at a greater magnification (right);

[0069] Figure 5 is the XRD of AGF prepared in Example 3 of the present invention;

[0070] Figure 6 is an X-ray photoelectron spectroscopy (XPS) diagram of the GF prepared in Example 1 of the present invention and the AGF prepared in Example 3;

[0071] Figure 7 It is a comparison diagram of the compression and recovery process of the AGF loaded with 1000g weight and the folding and recovery process of the cut piece prepared in Example 3 of the present invention;

[0072] Figure 81 is a stress-strain diagram of the GF prepared in Example 1 of the present invention and the AGF prepared in Example 3 under 97% compressive strain;

[0073] Fig. 9 is a FESEM image of the copper-loaded reduced GO foam (CGF) prepared in Example 4 of the present invention and the corresponding element distribution image;

[0074] Fig.10 is a FESEM image of the silver-loaded reduced GO foam (AGFⅡ) prepared by two-step reduction in Example 5 of the present invention;

[0075] Fig.11 The half-cells assembled with GF loaded with different functional particles prepared in Test Examples 1, 2, 3 and 4 of the present invention as the positive electrode of aqueous zinc ion battery and zinc sheet as the negative electrode were tested at 1 mA cm -2 Voltage distribution curve under current density;

[0076] Fig.12 The GF and AGF prepared in Test Examples 1, 2 and 3 of the present invention are used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet is used as the negative electrode to assemble the half-cell. At a current density of 5 mA cm -2 Coulomb efficiency diagram below;

[0077] Fig.13 The AGF prepared in Test Example 5 of the present invention is used as a zinc metal carrier in combination with ammonium vanadate (NH4V4O 10 , represented by NVO) positive electrode assembled full battery cycle performance diagram;

[0078] Fig.14 The AGF@Zn||NVO soft-pack battery prepared in Test Example 6 of the present invention is subjected to a deep-sea environmental pressure simulation test;

[0079] Fig.15 The AGFⅡ prepared in Test Example 7 of the present invention is used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet is used as the negative electrode to assemble the half-cell. -2 Coulomb efficiency diagram below. DETAILED DESCRIPTION

[0080] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0081] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0082] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0083] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0084] Example 1

[0085] Preparation of GF:

[0086] 120 mg of ascorbic acid (AA) was dissolved in 1.6 mL of deionized water, named solution A (reducing agent solution); 1 g of sodium dodecyl sulfate (SDS) was dissolved in 5 mL of deionized water, named solution B (surfactant solution); 75 mg of graphene oxide (GO) was dispersed in 5 mL of deionized water, named solution C; Solution A was stirred at 0.05 mL min -1 The mixture was injected into solution C at a speed of 10 μL, and then 10 μL of solution B was added. The mixture was stirred at 2000 rpm for 5 minutes, poured into a container, and hydrothermally assembled at 80°C for 12 hours to obtain a reduced GO hydrogel. The obtained hydrothermal product was placed in a refrigerator and completely frozen (freezing temperature -18°C, time 12 hours), and thawed at room temperature for 6 hours to obtain a GF precursor. GF was obtained through a wet compression strategy (i.e., placing the material between two glass plates, squeezing the two glass plates to 10% of the original height) and an air drying process.

[0087] Figure 1 The FESEM cross-sectional view (left) and TEM plan view (right) of the GF precursor prepared in Example 1 of the present invention are shown in the figure. It can be seen from the figure that the GF precursor has a uniform macroporous structure with a pore size range of about 20 μm-300 μm and an average diameter of about 100 μm. Due to the presence of two templates, air bubbles and ice crystals, during the freezing process, the ice crystals will penetrate the pore walls of the macroporous structure to form a three-dimensional interconnected pore structure.

[0088] Example 2

[0089] Preparation of SGF:

[0090] The GF slices prepared in Example 1 (area 1.13 cm 2, thickness 200μm) for standby; 0.9g urea and 0.133g potassium stannate were dissolved in 20mL deionized water, stirred for 30 minutes, then 20mL ethanol was added, stirred for 2 hours, and then the GF slices (10 slices) prepared in Example 1 were added for hydrothermal reaction at 170℃ for 1h. Rinse with water and ethanol solution several times, dry, and obtain reduced GO aerogel loaded with tin dioxide (SnO2); then put it into a tubular furnace, calcine at 700℃ for 4h in a reducing atmosphere (nitrogen and hydrogen, where the flow ratio of nitrogen and hydrogen is (19:1), and finally obtain SGF, in which the loading amount of tin particles on the three-dimensional foam carbon carrier is about 35wt%.

[0091] Figure 2 This is a FESEM plan view of the SGF prepared in Example 2 of the present invention (right), from which it can be seen that the tin particles in the SGF are evenly distributed on the surface of the GF material.

[0092] Figure 3 This is the XRD diagram of the SGF prepared in Example 2 of the present invention, which verifies the successful introduction of the tin element.

[0093] Example 3

[0094] Preparation of AGF:

[0095] 120 mg AA was dissolved in 1.6 mL deionized water, named solution A; 1 g SDS was dissolved in 5 mL deionized water, named solution B; 600 μL silver ammonia solution (0.1 M) was ultrasonically dispersed in 5 mL GO (15 mg mL -1 ) solution, named solution C; then solution A was added at 0.05 mL min -1 The reaction mixture was injected into solution C at a speed of 2000 rpm, and then 10 μL of solution B was added. The mixture was stirred at 2000 rpm for 5 minutes, poured into a container, and hydrothermally assembled at 80°C for 12 hours to obtain silver-loaded reduced GO hydrogel. The hydrothermal product was then placed in a refrigerator and frozen for 12 hours to completely freeze it, and thawed at room temperature for 6 hours. AGF was obtained through a wet compression strategy (i.e., placing the material between two glass plates and squeezing the two glass plates to 10% of the original height) and an air drying process, in which the loading amount of silver particles on the three-dimensional foam carbon carrier was about 10 wt%.

[0096] Figure 4The FESEM cross-sectional view before wet compression (left) and after wet compression (middle) of AGF prepared in Example 3 of the present invention, as well as the morphology at a higher magnification (right), show that the morphology of AGF before wet compression is also a typical macroporous structure with an average pore size of about 100 μm, and the structure is similar to that of GF material without the introduction of silver. In contrast, after the wet compression process, AGF presents a dense layered structure, which greatly enhances its strength. In addition, from the morphology at a higher magnification, it can be seen that silver is evenly distributed on graphene without obvious agglomeration.

[0097] Figure 5 This is the XRD diagram of the AGF prepared in Example 3 of the present invention, which verifies the successful introduction of the silver element.

[0098] Figure 6 It is the XPS graph of GF prepared in Example 1 of the present invention and AGF prepared in Example 3. The CO peak, C=C peak and OC=O peak are shifted, which verifies the interaction between silver and graphene.

[0099] Figure 7 The figure is a comparison of the compression and recovery process of the AGF loaded with 1000g weight and the folding and recovery process of the cut piece made in Example 3 of the present invention. After being compressed for a period of time, when the weight is removed, the AGF can quickly recover to its original height; after being folded more than 90 degrees, the AGF cut piece can also quickly recover to its original state, demonstrating its excellent pressure resistance and elasticity.

[0100] Figure 8 It is the compressive strength of GF prepared in Example 1 of the present invention and AGF prepared in Example 3 at 97% strain. The compressive strength of the above-mentioned AGF material of the present invention at 97% strain is 150MPa, which is significantly better than the compressive strength of GF, indicating that the metal nanoparticles have an improving effect on the mechanical strength of the three-dimensional foam carbon carrier. In summary, it can be seen that the electrode of the present invention can withstand load-holding fatigue and can realize energy storage applications in extreme environments.

[0101] Example 4

[0102] Preparation of CGF:

[0103] Compared with Example 3, the difference is that the silver ammonia solution in solution C is changed to copper ammonia solution, and the rest of the process is detailed in Example 3, wherein the loading amount of copper particles on the three-dimensional foam carbon carrier is 6 wt%.

[0104] Fig. 9 It is a FESEM cross-sectional view and a corresponding element distribution image of the CGF prepared in Example 4 of the present invention. The morphology of the CGF is also a typical macroporous structure, and the copper element is evenly distributed inside the material.

[0105] Example 5

[0106] The GF slices prepared in Example 1 (area 1.13 cm 2 , thickness 200μm) for later use; add 600μL silver ammonia solution (0.1M) to 20mL deionized water, then add GF slices (75mg) prepared in Example 1, and then slowly add AA (40mg). Rinse with water and ethanol solution several times, dry, and obtain silver-loaded reduced GO aerogel (AGFⅡ). (Because of the two-step reduction method, GO has been reduced to rGO, so the amount of reducing agent ascorbic acid is small)

[0107] Fig.10 This is the FESEM image of AGFⅡ prepared in Example 5 of the present invention. It can be seen that the Ag particles have undergone a certain degree of agglomeration. Therefore, the uniformity of introducing metal substances by the one-step reduction method shown in Example 3 is better than that of Example 5.

[0108] Test Example 1

[0109] The GF prepared in Example 1 was used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet was used as the negative electrode to assemble a half-cell (when assembling the half-cell, the negative electrode carrier was used as the positive electrode. When the zinc ion battery was actually prepared, the GF was used as the negative electrode. The following test examples were also the same, which will not be repeated here). The electrolyte used was zinc sulfate with a concentration of 2M, and the diaphragm was a glass fiber diaphragm. After the assembly was completed, the battery was first placed in a constant temperature room for 2 hours, and then the electrochemical test was performed.

[0110] Test Example 2:

[0111] The SGF prepared in Example 2 was used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet was used as the negative electrode to assemble the half-cell. The electrolyte used was zinc sulfate with a concentration of 2M, and the diaphragm was a glass fiber diaphragm. After the assembly was completed, the battery was first placed in a constant temperature room for 2 hours, and then the electrochemical test was performed.

[0112] Test Example 3

[0113] The AGF prepared in Example 3 was used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet was used as the negative electrode to assemble a half-cell. The electrolyte used was zinc sulfate with a concentration of 2M, and the diaphragm was a glass fiber diaphragm. After the assembly was completed, the battery was first placed in a constant temperature room for 2 hours, and then an electrochemical test was performed.

[0114] Test Example 4

[0115] The CGF prepared in Example 4 was used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet was used as the negative electrode to assemble a half-cell. The electrolyte used was zinc sulfate with a concentration of 2M, and the diaphragm was a glass fiber diaphragm. After the assembly was completed, the battery was first placed in a constant temperature room for 2 hours, and then an electrochemical test was performed.

[0116] Fig.11 The reduced GF loaded with different functional particles prepared in Test Examples 1, 2, 3 and 4 of the present invention is used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet is used as the negative electrode to assemble the half-cell. -2 Voltage distribution curve under current density. It can be seen from the figure that compared with the original GF, the nucleation overpotential of SGF, AGF and CGF loaded with functional particles during the deposition process has decreased, proving that the introduction of different functional zinc-philic particles can effectively reduce the nucleation overpotential of metallic zinc, thereby making metallic zinc deposited evenly and preventing the formation of zinc dendrites.

[0117] Fig.12 The GF, SGF and AGF prepared in Test Examples 1, 2 and 3 of the present invention are used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet is used as the negative electrode to assemble the half-cell. At a current density of 5 mA cm -2 From the Coulomb efficiency graph below, it can be seen that AGF has the best cycle stability and a higher average Coulomb efficiency of 99.5%, followed by SGF, and finally GF.

[0118] Test Example 5

[0119] The AGF prepared in Example 3 was subjected to 12 mAh cm -2 After the pre-deposition of the capacity, the full battery is assembled as the negative electrode. Ammonium vanadate (NVO) is used as the positive electrode. The preparation method of the NVO positive electrode sheet is as follows: at room temperature, a slurry is prepared according to the mass ratio of NVO:Super-P:PVDF=7:2:1 and evenly scraped on the titanium foil, then placed in a vacuum oven at 80℃ and dried for 10 hours, and then punched into the size of the electrode sheet to obtain the positive electrode.

[0120] Fig.13 The cycle performance diagram of the full battery assembled in Test Example 5 of the present invention is shown in Figure 5. -1 It can still stably cycle more than 2500 times at a high current density, indicating that the special carbon-based foam material prepared by the present invention realizes uniform and controllable zinc deposition / stripping behavior through three-dimensional structure design combined with the introduction of zinc-philic particles, effectively inhibits the occurrence of side reactions, and achieves good cycle stability.

[0121] Test Example 6

[0122] The AGF prepared in Example 3 was subjected to 12 mAh cm -2After the pre-deposition of the capacity, the negative electrode was used, and NVO was used as the positive electrode to assemble the soft pack battery. A deep-sea pressure simulation test was carried out on a deep-sea pressure environment simulation device (SUP_RGXT_100, Jinan Simingte Co., Ltd.). The AGF@Zn||NVO soft pack battery was placed in the test device, and the simulated pressure was set to 50MPa. After 3600s, the pressure was removed and the soft pack battery was taken out for lighting test.

[0123] Fig.14 The deep-sea environmental pressure simulation test was carried out using soft-pack batteries. After continuous pressure loading and unloading processes, the AGF@Zn||NVO soft-pack batteries can still power the light-emitting diode device well.

[0124] Test Example 7

[0125] The AGFⅡ prepared in Example 5 was used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet was used as the negative electrode to assemble a half-cell. The electrolyte used was zinc sulfate with a concentration of 2M, and the separator was a glass fiber separator. After the assembly was completed, the battery was first placed in a constant temperature room for 2 hours, and then an electrochemical test was performed.

[0126] Fig.15 The AGFⅡ prepared in Test Example 7 of the present invention is used as the positive electrode of the aqueous zinc ion battery, and the zinc sheet is used as the negative electrode to assemble the half-cell. At a current density of 5 mA cm -2 The Coulomb efficiency diagram below shows that compared with AGF, the cyclic stability of AGFⅡ is poor, which proves that the silver particles generated by the one-step reduction method are evenly distributed and have better electrochemical performance.

[0127] Comparative Example 1

[0128] 120 mg AA was dissolved in 1.6 mL deionized water, named solution A; 1 g SDS was dissolved in 5 mL deionized water, named solution B; 600 μL silver ammonia solution (0.1 M) was ultrasonically dispersed in 5 mL GO (15 mg mL-1) solution, named solution C; then solution A was heated at 0.05 mL min -1 The mixture was injected into solution C at a speed of 10 μL, and then 10 μL of solution B was added. The mixture was stirred at 2000 rpm for 5 minutes, poured into a container, and hydrothermally assembled at 80°C for 12 hours to obtain silver-loaded GO hydrogel. The hydrothermal product was then placed in a refrigerator and frozen for 12 hours to completely freeze, thawed at room temperature for 6 hours, and dried in air.

[0129] The comparative example was subjected to a compression test. After a period of compression by a heavy object, when the weight was removed, it could not return to its original height, showing plastic deformation. By comparing the results of comparative example 1 with those of example 3, it can be seen that the present invention can only improve the mechanical properties of the three-dimensional foam carbon carrier better after the ice crystal template is introduced by freezing and extrusion treatment, and the ice crystals squeeze and pierce the hydrogel network to form a three-dimensional interconnected pore structure.

[0130] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0131] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0132] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0133] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A fatigue-resistant special carbon-based foam material, characterized in that: The anti-fatigue special carbon-based foam material comprises a three-dimensional foam carbon support and optionally functional particles loaded on the three-dimensional carbon support; the functional particles are metal nanoparticles that can provide additional zinc-philic sites to induce zinc deposition.

2. The anti-fatigue special carbon-based foam material according to claim 1, characterized in that: The functional particles are selected from at least one of tin, copper or silver nanoparticles; and / or, The loading amount of the functional particles on the three-dimensional foam carbon carrier is 2 wt% to 20 wt%; and / or, The pore size of the three-dimensional foam carbon carrier ranges from 20 μm to 300 μm.

3. A method for preparing a fatigue-resistant special carbon-based foam material, characterized in that: The following steps are involved: After introducing a bubble template into an optional solution containing a functional particle precursor and a carbon material aqueous solution, hydrothermal assembly is performed; freezing the hydrothermally assembled material and introducing it into an ice crystal template and extruding it to obtain a three-dimensional foam carbon carrier or the anti-fatigue special carbon-based foam material; optionally loading functional particles onto the three-dimensional foam carbon carrier; obtaining the anti-fatigue special carbon-based foam material; The anti-fatigue special carbon-based foam material described in any one of claims 1 to 2 is preferably prepared by the method described.

4. The method for preparing the anti-fatigue special carbon-based foam material according to claim 3, characterized in that: The following steps are involved: Step (1): mixing an optional solution containing a functional particle precursor with an aqueous solution of a carbon material; and then mixing them evenly with a reducing agent and a surfactant to obtain a foamed carbon material solution; Step (2): hydrothermally assembling the foam carbon material solution to obtain a three-dimensional foam carbon hydrogel; Step (3): freezing, extruding, thawing, and drying the three-dimensional carbon foam hydrogel to obtain a three-dimensional carbon foam carrier or the anti-fatigue special carbon-based foam material; Optional step (4): after mixing the reducing agent and the solution containing the functional particle precursor evenly, add an optional hydrothermal solvent and mix evenly; then add the slices of the three-dimensional foam carbon carrier to react, wash, dry, and optionally calcine in a reducing atmosphere; to obtain the anti-fatigue special carbon-based foam material.

5. The method for preparing the anti-fatigue special carbon-based foam material according to claim 4, characterized in that: In step (1), The carbon material used is a carbon material having self-assembly and / or gelation capabilities; preferably, the carbon material is selected from at least one of graphene oxide, carbon nanotubes or transition metal carbides; and / or, The solution containing the functional particle precursor in step (1) is a solution containing at least one of silver, copper and tin metal ions, preferably at least one of a silver ammonia solution, a copper ammonia solution or a potassium stannate solution; and / or, The surfactant is selected from at least one of sodium lauryl sulfate, polyvinyl pyrrolidone, alkyl glycoside, polyethylene glycol ether or lauryl alcohol chloride; and / or, The reducing agent is selected from at least one of ascorbic acid, hydrazine hydrate or urea; and / or, In step (1), the solution containing the reducing agent is first injected and mixed evenly, and then the solution containing the surfactant is added and mixed evenly; preferably, the injection rate is 0.02-0.15 mL min -1 , more preferably 0.03 to 0.1 mL min -1 and / or, In step (1), the mixing is carried out by vigorous stirring; preferably, the stirring speed is 500 to 3000 rpm, more preferably 1600 to 2400 rpm; and / or, the stirring time is 2 to 30 min, preferably 2 to 15 min; and / or, The ratio of the carbon material to the surfactant is (30-120) mg: (0.5-5) mg; preferably (50-80) mg: (1.5-3) mg; and / or, The ratio of the carbon material to the functional particle precursor is (30-120) mg: (10-140) mg; preferably (50-80) mg: (10-30) mg; and / or, The ratio of the carbon material to the reducing agent is (30-120) mg: (40-180) mg; preferably (50-80) mg: (60-130) mg; and / or, The mass volume ratio of the carbon material to the total volume of the solvent used in the system of step (1) is (30-120) mg: (5-15 mL).

6. The method for preparing the anti-fatigue special carbon-based foam material according to claim 4, characterized in that: In step (2), The hydrothermal assembly temperature is 50 to 120° C., preferably 60 to 100° C.; and / or, The hydrothermal assembly time is 2 to 24 hours, preferably 5 to 15 hours; and / or, In step (3), The freezing temperature is -50 to 15°C, preferably -30 to 15°C; and / or, The freezing time is 2 to 20 hours, preferably 4 to 15 hours; and / or, The extrusion refers to extrusion to 10% to 50% of the original height; and / or, The thawing temperature is room temperature; and / or, The drying is air drying at room temperature.

7. The method for preparing the anti-fatigue special carbon-based foam material according to claim 4, characterized in that: In step (4), The hydrothermal solvent is selected from at least one of ethanol and water; and / or, The reducing agent is selected from at least one of ascorbic acid, hydrazine hydrate or urea; and / or, The solution containing the functional particle precursor in step (4) is a solution containing at least one of silver, copper, and tin metal ions, preferably at least one of a silver ammonia solution, a copper ammonia solution, or a potassium stannate solution; and / or, In step (4), the mass ratio of the functional particle precursor to the reducing agent is (1-200) mg:(40-180) mg; preferably (5-150) mg:(60-130) mg; and / or, The mass ratio of the functional particle precursor to the hydrothermal solvent is (1-200) mg: (10-80) g; preferably (5-150) mg: (20-40) g; and / or, The mass ratio of the functional particle precursor to the three-dimensional foam carbon carrier is (1-200) mg: (3-130) mg; preferably (5-150) mg: (3-100) mg; and / or, In step (4), the reaction is a hydrothermal reaction or a reaction at room temperature. Preferably, the temperature of the hydrothermal reaction is 80 to 200° C.; preferably 80 to 170° C.; and / or, the time of the hydrothermal reaction is 1 to 24 hours; preferably 1 to 12 hours; and / or, The reducing atmosphere at least comprises hydrogen; the calcination temperature is 500 to 800° C., preferably 600 to 700° C.; and / or, The calcination time is 1 to 6 hours, preferably 1 to 4 hours.

8. Use of the anti-fatigue special carbon-based foam material as described in any one of claims 1 to 2 or the anti-fatigue special carbon-based foam material prepared by the method according to any one of claims 3 to 7 in a battery, preferably in a zinc ion battery, and more preferably as a zinc metal negative electrode carrier.

9. A zinc metal negative electrode carrier, characterized in that: The material of the zinc metal negative electrode carrier includes the anti-fatigue special carbon-based foam material according to any one of claims 1-2 or the anti-fatigue special carbon-based foam material prepared by the method according to any one of claims 3-6.

10. A zinc ion battery, characterized in that: The material of the zinc metal negative electrode of the zinc ion battery includes the anti-fatigue special carbon-based foam material according to any one of claims 1-2 or the anti-fatigue special carbon-based foam material prepared by the method according to any one of claims 3-6.